Antidiabetic Effectiveness Test of Andaliman Fruit (Zanthoxylum acanthopodium) Extract on Histopathological Changes in Peripheral Nerves: An In Vivo Study - Larisma Simanullang; Sionia Delaroza Doloksaribu; Riyani Susan Bt. Hasan; Boyke Marthin Simbolon (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: Diabetes mellitus (DM) is a chronic metabolic disease characterized by elevated blood sugar levels, and the increase in sugar levels is triggered by low insulin production or the ineffective use of insulin by the body (relatively). Diabetic neuropathy is a complication that often attacks DM patients and is the highest complication of diabetes. This study aims to test the effectiveness of Andaliman fruit (Zanthoxylum acanthopodium) extract on the improved histopathology of Peripheral nerve in alloxan-induced Wistar rats (Rattus norvegicus). Methods: This study is an experimental study using 24 Wistar rats, which were grouped into 6 groups (1: normal, 2: negative control, 3: positive control, 4-6: DM + andaliman extract 150mg/kgBW, 250 mg/kgBW, 350 mg /kgBB). Data analysis used SPSS to determine differences in the histological conditions of peripheral nerves. Results: The administration of andaliman fruit extract at a dose of 350 mg/kgBW was most effective in inhibiting the proliferation of Schwann cells, which showed the potential of andaliman fruit extract in preventing the progression of diabetic neuropathy. The administration of andaliman fruit extract at a dose of 350 mg/kgBW also showed the most effective potential in inhibiting the inflammatory process in the peripheral nerves, which is believed to be responsible for peripheral nerve cell damage. Conclusion: Andaliman fruit (Zanthoxylum acanthopodium) extract is effective against improving the histopathology of peripheral nerves in alloxane-induced Wistar rats (Rattus norvegicus).